Colloids created by light: Laser-generated nanoparticles for applications in biology and medicine. (2017) - Kalus, Mark-Robert; Rehbock, Christoph; Bärsch, Niko; Barcikowski, Stephan
Abstract: Nanomaterials play a major role in today's research and have become almost indispensable in the field of biology and medicine. However, nanomaterials used in biomedicine must meet specific criteria, among which purity has the highest priority, as it ensures maximum biocompatibility. This brief review article is intended to introduce laser ablation in liquids as a facile and rapid method for the preparation of high-purity colloidal nanoparticles. In this context, a brief introduction into the physics of the laser ablation process as well as into the unique properties of the generated nanoparticles is given, while the main focus of this article lies on the applicability of laser-fabricated nanomaterials in biology and medicine, which is illustrated with recent examples.